2023
DOI: 10.3390/polym15081938
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of the Mixing of Highly Viscous Polymer Suspensions in Partially Filled Sigma Blade Mixers

Abstract: This paper presents a non-isothermal, non-Newtonian Computational Fluid Dynamics (CFD) model for the mixing of a highly viscous polymer suspension in a partially filled sigma blade mixer. The model accounts for viscous heating and the free surface of the suspension. The rheological model is found by calibration with experimental temperature measurements. Subsequently, the model is exploited to study the effect of applying heat both before and during mixing on the suspension’s mixing quality. Two mixing indexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Rotational flow dominates at the edge of the blade, and the material and blades rotate synchronously without deformation, also known as the "dead zone" of flow. Larsen et al 21 presented a non-isothermal, non-Newtonian computational fluid dynamics (CFD) model, which can be used in the simulation of highly viscous polymer suspensions in a partially filled twin-sigma mixer. The results revealed that the dispersive mixing and distributive mixing were hardly affected by changing the wall temperature and preheating temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Rotational flow dominates at the edge of the blade, and the material and blades rotate synchronously without deformation, also known as the "dead zone" of flow. Larsen et al 21 presented a non-isothermal, non-Newtonian computational fluid dynamics (CFD) model, which can be used in the simulation of highly viscous polymer suspensions in a partially filled twin-sigma mixer. The results revealed that the dispersive mixing and distributive mixing were hardly affected by changing the wall temperature and preheating temperature.…”
Section: Introductionmentioning
confidence: 99%
“…This newly developed numerical method proved its effectiveness in handling complex fluid flow scenarios, including confined flows and extrudate swell simulations of Boger fluids. Larsen et al [ 2 ] presented a non-isothermal, non-Newtonian Computational Fluid Dynamics model for the mixing of a highly viscous polymer suspension in a partially filled sigma blade mixer. This model accounts for viscous heating and the free surface of the suspension.…”
mentioning
confidence: 99%